Pengaruh Penggunaan Media Mini Flashcard Terhadap Penguasaan Kosakata Bahasa Inggris Siswa Kelas III Sekolah Dasar - Nur Wafiroh; Ulhaq Zuhdi; Wahyu Sukartiningsih; Nurul Istiq’faroh (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
Vocabulary mastery is an essential foundation in learning English at the elementary school level. However, many students still experience difficulties in understanding and remembering vocabulary because learning activities tend to rely on conventional methods. This study aimed to analyze the effect of using mini flashcard media on the English vocabulary mastery of third-grade elementary school students. The research employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design. The sample consisted of 39 third-grade students of SDN Kepatihan Lamongan, including 20 students in the experimental class and 19 students in the control class. Data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, an independent samples t-test, and an N-Gain test. The results showed that the data were normally distributed and homogeneous. The hypothesis test obtained a significance value (Sig. 2-tailed) of 0.430 (p>0.05), indicating that the use of mini flashcards did not have a significant effect on students’ English vocabulary mastery. Nevertheless, the N-Gain score of 0.3791 indicated a moderate improvement. Therefore, mini flashcards have not been proven to produce a significant effect, but they have the potential to support more engaging vocabulary learning and moderately improve students’ vocabulary mastery.